Impact of Iron, Silicon and Boron Nanoparticles on the AC Breakdown Voltage of Rice Bran Oil in the Presence of CTAB - Mohd Taufiq Ishak; Nur Sabrina Suhaimi; Nurul ‘Izzati Hashim; Ja’afar Adnan; Fakroul Ridzuan Hashim (Semarak Ilmu Publishing, 2026)
Non-Indexed Publication